Pengaruh Gaya Hidup, Uang Saku, dan Tren terhadap Perilaku Belanja Online Mahasiswa - Parmini*, Parmini; Hernowo, Bingar (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Online shopping behavior makes shopping can be done at any time, anywhere, and conditions that allow. The price factor is also very influential in online shopping, to the availability of various products offered on online sites. The existence of e-commerce is necessary to get a good understanding of the factors that can influence online buying behavior, it can even help online marketers to improve their applications. Lifestyle, pocket money, and trends are factors that are believed to influence student online shopping behavior, so that all three need to be studied in depth. The results are expected to be used as a reference for business people to see students as a unique market opportunity with all its dynamics. The purpose of this study was to see the effect of lifestyle, pocket money, and trends on online shopping behavior of students in Yogyakarta. This type of research is a quantitative correlational method with a population of students in Yogyakarta through a purposive sampling technique. The results of the research based on the Spearman rank test show that lifestyle, trends, and pocket money influence students' online shopping behavior